Analysis of the degradation of single‐crystalline silicon modules after 21 years of operation. (19th April 2021) - Piliougine, Michel; Oukaja, Amal; Sánchez‐Friera, Paula; Petrone, Giovanni; Sánchez‐Pacheco, Francisco José; Spagnuolo, Giovanni; Sidrach‐de‐Cardona, Mariano
Abstract: In this paper, the results of the analysis of the degradation of a set of single‐crystalline silicon modules after 21 years are presented. The comparison of the main electrical parameters and the series and of the shunt resistances measured in 1996 and 2017 is performed, so that the annual degradation rate is evaluated. In addition, a detailed analysis of the parameter uncertainties has been performed in order to determine its impact on the results. A visual inspection of the modules has also been carried out in order to show the correlation with the variation of the electrical performance. Finally, the temperature coefficients of the degraded modules have been estimated and compared with the nominal ones. The results shown in the paper reveal that the mean annual degradation rate in terms of power is close to 0.9%. Abstract : The degradation of single‐crystalline silicon modules after 21 years is studied by the comparison of the main electrical parameters and parasitic resistances, and the annual degradation rates are evaluated. A visual inspection of the modules has also been carried out in order to show the correlation with the variation of the electrical performance. The results shown in the paper reveal that the mean annual degradation rate in terms of power is close to 0.9%.